Growth and shear loss characteristics of an aerobic biofilm : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Technology in Biotechnology at Massey University - See, Tiam Teng (Massey University, 1990)
The application of biofilms in fermentation and waste treatment processes has been increasingly considered in recent years due to several inherent advantages over suspended growth systems. For example, they enable higher biomass hold-up providing larger quantity of cell per unit reactor volume which allows high loading rates. The biofilm systems, with fixed or immobilised cells, avoid washout conditions. The often difficult problems of sludge thickening, separation, recycle, and wasting associated with suspended growth systems are eliminated for biofilm systems. However, the major drawback lies in the control of film thickness in order to maintain high reactor productivities. The attached film thickness depends on both the biological parameters such as growth rate, and physical parameters such as hydrodynamic shear. The understanding of the growth and shear loss characteristics is a prerequisite for effective film thickness control. The main objective of this work therefore is to investigate the growth and shear loss characteristics of an aerobic biofilm utilizing phenol in a concentric cylindrical bioreactor. The growth and detachment of the biofilm was studied at different shear stresses, and their relationships were established. Detachment by shear was studied under two different conditions. One was examined simultaneously with growth under a constant shear stress where the biofilm detachment and growth occurred at the same time in the bioreactor. The other was examined via a separate shear test performed on the biofilm initially grown at a shear stress lower than that applied during the test. A method for measuring the torque exerted on the biofilm surface was first developed to enable computation of the related shear stress necessary for the study. The effect of film thickness on torque at film surface for a constant rotational speed was not significant. Shear stress can be conveniently determined from a quadratic relationship between torque and rotational speed for the range of film thickness studied. The substrate consumption is directly proportional to film thickness up to about 0.050 to 0.100 mm only, and beyond that it becomes independent of film thickness. The mass transfer resistance in the liquid phase appears to reach a minimum at shear stress greater than 3.44 N/m2 coinciding with the maximum steady-state substrate removal rate. The shear loss resistance of the biofilm increases with increasing shear stress during growth. The ultimate shear loss rate and shear stress relationship follows approximately: Rs = (40.82 – 2.750+0.1502 – 31.83e-0.610 ) × 10-2 The net growth rate varies with shear stress according to a parabolic function which predicts a shear stress of 19 N/m2 is required to achieve zero net growth. The biofilm-support adhesion must remain stronger than the film layer adhesion, otherwise, detachment will occur at the film-support interface rendering it impossible to control the film thickness.
Keywords: Biofilms